2007
DOI: 10.1093/eurheartj/ehn141
|View full text |Cite
|
Sign up to set email alerts
|

Preserved left ventricular twist and circumferential deformation, but depressed longitudinal and radial deformation in patients with diastolic heart failure

Abstract: LV longitudinal and radial strains are reduced, but circumferential deformation and twist are normal in DHF patients. On the other hand, in patients with SHF, longitudinal, radial, and circumferential deformation, and twist are all reduced. Multivariable regression analysis suggests that preserved LV twist and circumferential strain may contribute to normal EF in patients with DHF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
306
10
14

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 390 publications
(360 citation statements)
references
References 23 publications
24
306
10
14
Order By: Relevance
“…In this study, the echocardiographic parameters did not differ between the mortality group and the survival group, except for GLS. In the nondialysis population, GLS is proved as a more reliable and sensitive parameter for representing LV systolic function in patients with cardiomyopathies, advanced-stage CKD, or HF with preserved LVEF (11,12,(27)(28)(29)(30). Less negative GLS is also proved as a powerful predictor of all-cause mortality in the general population (9), and is reported to be useful in the preclinical diagnosis of a number of other cardiomyopathies, including diabetes, hypertrophic cardiomyopathy, and amyloidosis (28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the echocardiographic parameters did not differ between the mortality group and the survival group, except for GLS. In the nondialysis population, GLS is proved as a more reliable and sensitive parameter for representing LV systolic function in patients with cardiomyopathies, advanced-stage CKD, or HF with preserved LVEF (11,12,(27)(28)(29)(30). Less negative GLS is also proved as a powerful predictor of all-cause mortality in the general population (9), and is reported to be useful in the preclinical diagnosis of a number of other cardiomyopathies, including diabetes, hypertrophic cardiomyopathy, and amyloidosis (28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities in each of these components have been identified in HFpEF with blunted exercise-induced increases in preload, blunted increases in ejection fraction, contractility and regional systolic function, impaired chronotropic reserve (i.e. chronotropic incompetence) and attenuated exercise-mediated vasodilatation being documented in several studies [15,16,18,41,42,[44][45][46][47]50,64,[92][93][94][95]. Recent studies have also reported increased prevalence of diastolic dyssynchrony in patients with HFpEF [96][97][98].…”
Section: Global Cardiovascular Reserve Dysfunctionmentioning
confidence: 99%
“…Whereas HFpEF is almost as common as heart failure with reduced ejection fraction, HFpEF has proven relatively refractory to treatment in a number of randomized clinical trials,13, 14, 15 underscoring the importance of efforts to better understand its pathophysiology. Interestingly, HFpEF has been related to both reduced GLS and increased aortic stiffness in a number of prior studies 3, 7, 16, 17, 18, 19, 20. Furthermore, both HFpEF and aortic stiffness are prevalent in older individuals, particularly women,16, 17 suggesting possible pathophysiologic links between aortic stiffness and subclinical alterations in LV systolic function that may promote the development of HFpEF in susceptible individuals.…”
Section: Introductionmentioning
confidence: 96%